Gender and the city before modernity - Foxhall, Lin; Neher, Gabriele (Gender & history (Unnumbered), 2012)
Gender and the city before modernity presents a series of multi-disciplinary readings that explore issues relating to the role of gender in a variety of cities of the ancient, medieval, and early modern worlds. Presents an inter-disciplinary collection of readings that reveal new insights into the intersection of gender, temporality, and urban space features a wide geographical and methodological range, includes numerous illustrations to enhance clarity.